The Influence of Entrepreneurial Self-Efficacy and Entrepreneurship Education on Entrepreneurial Intentions: A Systematic Review with PRISMA Framework and Quantitative Research Design - Eko Prasetyowati; Achmad Husen; Suparno Suparno (Dinasti Publisher, 2025)
This study investigates the influence of entrepreneurial self-efficacy and entrepreneurship education on entrepreneurial intentions using a systematic literature review (SLR) methodology, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). By applying a quantitative research design, this research synthesizes findings from relevant studies to assess how self-efficacy and educational interventions impact the development of entrepreneurial intentions. The PRISMA framework ensures a rigorous and transparent review process, enhancing the quality and reliability of the included studies. Only articles indexed in Scopus (Q1–Q4) were selected through the Watase Uake database. The findings reveal that higher levels of self-efficacy, in conjunction with targeted entrepreneurship education, significantly foster individuals' confidence in their entrepreneurial abilities and intentions. Additionally, institutional support and experiential learning are identified as key factors that further strengthen this relationship. This research contributes valuable insights into how self-efficacy and education shape entrepreneurial intentions, providing a solid foundation for advancing entrepreneurial education programs and policy development.